The habitus of digital scholars - Cristina Costa (Association for Learning Technology, 2014)
This article concerns the Participatory Web and the impact it has on academic researchers' perceptions of digital scholarship practices. The Participatory Web, as a space of active involvement, presence and socialisation of knowledge, has the potential to introduce significant changes to scholarly practice and to diversify it. This article draws on the findings of a narrative inquiry study that investigated the habitus of 10 digital scholars. The study uses Bourdieu's concepts of habitus, field, and social and cultural capital as a research lens. One of the main findings to come out of the study was that research participants' approaches to digital scholarship practices are highly influenced by their online social capital, the online networks that influence their thinking and outlook on scholarly practices, including their advocacy of openness and transparency of academic practice. This article concludes by highlighting the dispositions digital scholars display in an attempt to characterise the values and beliefs that underpin their scholarly practices.